Two cases of religious socialization among minorities. Issue 2 (3rd April 2019) - Broo, Måns; Kheir, Sawsan; Sarkar, Mallarika
ABSTRACT: Research indicates that religion is particularly important among minority groups (e.g., Pargament 2002). The current study focuses on religious socialization among young adults within two specific religious minorities, (1) Muslims in West Bengal, India, and (2) The Druze in Israel. Specifically, we aim at answering two questions: (a) are these religious minorities more successful at socialization than their corresponding majority religious communities, and (b) how do members of these minorities articulate their religion and socialization into it? Based on a mixed-method study, including survey responses and in-depth interviews, our results answer the first research question affirmatively for Muslims in India, and negatively for the Druze in Israel, suggesting the importance of relating to the specific contextual characteristics of each religious minority separately, and avoiding general conclusions. For both groups, family seems to be the major agent of socialization, and the impact of social media needs further exploration.